If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = -103 + -6x Reorder the terms: -3 + 4x = -103 + -6x Solving -3 + 4x = -103 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -3 + 4x + 6x = -103 + -6x + 6x Combine like terms: 4x + 6x = 10x -3 + 10x = -103 + -6x + 6x Combine like terms: -6x + 6x = 0 -3 + 10x = -103 + 0 -3 + 10x = -103 Add '3' to each side of the equation. -3 + 3 + 10x = -103 + 3 Combine like terms: -3 + 3 = 0 0 + 10x = -103 + 3 10x = -103 + 3 Combine like terms: -103 + 3 = -100 10x = -100 Divide each side by '10'. x = -10 Simplifying x = -10
| Y=-4x-16x+20 | | 2x+5-8w=7-4w | | 3m+3-m=3(m+1) | | -1v+5+4v=1+5v+3 | | (2i+3)(7i+6)= | | 9x+6(3x-4)=12-9x | | 3a-11=4(a+1)+13a+3 | | 2g-8+3g=7 | | .17(x+29)=86 | | 2x-6=5x+27 | | 2y^2-7y-10=0 | | 4x-2(.50-1)=14 | | 101(87+13)= | | y^3+729= | | 4x-2(x-2)=-7+4x+5 | | 9x-12=84 | | 4(2x-3)=30 | | 15-12z=21 | | .17(x-29)=86 | | 2x=1-5 | | 7(x+2)=5(x+14) | | p-4=-1+2P | | 4m+8m=84 | | 2(m-8)=12 | | 9k(8k+7)= | | 10x+44=2(8x-23) | | T+4=120 | | 10-2x=-2y | | 77x^2-145+50= | | 9(x-7)+54=9x-8 | | 2(m-8)=54 | | 16-n=2n+8+5n |